Multifunctional PVA-CS/LaB6-MXene fiber nanocomposites: Improved thermal, electrical and biological properties - Erol, Ibrahim; Ismail, Ibrahim; Demirelli, Kadir; Aksu, Mecit; Guney, Bekir (Elsevier, 2025)
This study produced fiber nanocomposites by adding 5 % lanthanum hexaboride nanoparticles (LaB6 NPs) and MXene (Ti3C2Tx) at different weight ratios (5, 7, and 10 w/w) to a polyvinyl alcohol (PVA)-chitosan (CS) polymer matrix via electrospinning. Structural analyses showed that the additives were homogeneously distributed and the crystalline phases were preserved. Thermal analyses revealed that with a 10 % MXene addition, the decomposition temperature increased by approximately 35 degrees C to T10 = 295 degrees C and T50 = 370 degrees C, while the residue ratio increased from 5.2 % to 13.4 %. In DSC analysis, the glass transition temperature (Tg) was 63 degrees C for PVA-CS/LaB6, while it increased to 79 degrees C for 10 % MXene. Contact angle measurements showed that the angles ranged from 39.80 degrees to 45.42 degrees for water and 25.53 degrees-30.17 degrees for diiodomethane (DIM). Surface free energy (SFE) decreased from 63.95 mN/m to 59.23 mN/m at 5 % MXene and increased again to 61.83 mN/m at 10 % MXene. Dielectric measurements revealed that the dielectric constant (epsilon ') increased from 5.0 to 11.3 at a low frequency (1 kHz) and ranged from 3.6 to 7.1 at a high frequency (1 MHz). AC conductivity (sigma ac) increased from 2.4 x 10- 7 S/cm to 1.1 x 10-6 S/cm at 1 kHz. In biological analyses, DPPH radical scavenging capacity increased from 20 % for 5 % LaB6-incorporated PVA-CS to 47 % for 10 % MXene. In antimicrobial tests, the inhibition zone diameter against S. aureus increased from 11.1 mm to 13.6 mm, E. coli from 9.1 mm to 11.3 mm, and C. albicans from 7.2 mm to 9.9 mm. The incorporation of MXene markedly enhanced the dielectric, thermal, surface, antioxidant, and antimicrobial features of the PVA-CS/LaB6 nanofibers. Taken together, these improvements point to a versatile material platform that can be tailored for various applications, including energy storage, EMI shielding, biomedical coatings, and active food packaging.
Keywords: PVA; Chitosan; LaB6; Mxene; electrospinning; Dielectric properties; Biological activity